Direct Election of President and Vice President In Pancasila Perspective - Sonny Taufan; Risang Pujiyanto (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractAfter the amendment to the 1945 Constitution of the Republic of Indonesia, the Election of President and Vice President was not conducted by the People's Consultative Assembly but voted directly by the people. Amendment to the provision for the election of President and Vice President have invited debate, partly because they are deemed incompatible with Pancasila. This study examines the appropriateness of the presidential and vice-presidential election based on Pancasila. The research method uses normative juridical, using secondary data obtained through literature study and qualitative analysis. The result and discussion of this research are that the implementation of the election of President and Vice President based is in accordance with Pancasila, especially with the fourth principle.Keywords: Democracy, Direct Election, and Pancasila AbstrakSetelah amandemen Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, Pemilihan Presiden dan Wakil Presiden tidak dilakukan oleh Majelis Permusyawaratan Rakyat tetapi dilaksanakan langsung oleh rakyat. Amandemen terhadap ketentuan untuk pemilihan Presiden dan Wakil Presiden telah mengundang perdebatan, sebagian karena mereka dianggap tidak sesuai dengan Pancasila. Studi ini mengkaji kelayakan ketentuan pemilihan presiden dan wakil presiden berdasarkan Pancasila. Metode penelitian menggunakan metode yuridis normatif, menggunakan data sekunder yang diperoleh melalui studi literatur dan dianalisis secara kualitatif. Hasil dan pembahasan penelitian ini adalah bahwa pelaksanaan pemilihan Presiden dan Wakil Presiden berdasarkan Pancasila sudah sesuai dengan Pancasila, terutama dengan prinsip keempatKata Kunci: Demokrasi, Pemilihan Langsung, Presiden dan Wakil Presiden, Pancasila. АннотацияПосле внесения поправки в Конституцию Республики Индонезия 1945 года выборы президента и вице-президента не проводились Народной Консультативной Ассамблеей, а проводились непосредственно всенародными выборами в Индонезии. Поправки к положениям о выборах президента и вице-президента вызвали дебаты, отчасти потому, что они считаются несовместимыми с Панчасилой. В этом исследовании рассматривается соответствие принятия положений о президентских и вице-президентских выборах на основе Панчасилы. Метод исследования – нормативно-юридический, используя вторичные данные, полученные в результате изучения литературы и проанализируемые качественным методом. Результаты и обсуждение этого исследования заключаются в том, что осуществление выборов президента и вице-президента на основе Панчасилы соответствует Панчасиле, особенно четвёртому принципу.Ключевые слова: Демократия, Прямые Выборы, Президент и Вице-Президент, Панчасила.